Marquard von Lindau and the challenges of religious life in late medieval Germany the Passion, the Eucharist, the Virgin Mary - Mossman, Stephen, 1979- (Oxford : Oxford University Press, 2010)
A study of Marquard von Lindau, arguably the most widely read author in German before the Reformation. Active in the second half of the 14th century, in the generation after the Black Death, Marquard made a distinctive and critical contribution to contemporary understanding of Christ's Passion, the Eucharist and the Virgin Mary.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Marquard, -- von Lindau, -- d. 1392.; Bible -- Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.; Jesus Christ -- Passion; Mary, -- Blessed Virgin, Saint; Lord's Supper -- History -- Middle Ages, 600-1500.